Pengaruh Jumlah dan Posisi Pemasangan Guide Vanes Pada Elbow Ducting Terhadap Besarnya Pressure Drop - A.A.N.B Mulawarman; I Gusti Bagus Wijaya Kusuma (Department of Mechanical Engineering, University of Udayana, 2012)
Duct system is connecting between the refrigeration system and room to be conditioned. Room airstreamed into the cooling coil through the return duct intake, air filters. Furthermore, the air sucked by theblower, which flowed into the evaporator. Through the register box, air conditioned which has flowed backinto the room. When flowing inside the duct, the air has obstacle. One inhibiting factor is the change indirection of flow due to bends. That occurs at elbow is caused by friction (friction loss) and flow separation(separation loss). The aims of this research is to examine the phenomenon of the flow with Re = 3824 x104 on a rectangular elbow as well as knowing how to influence the guide vanes at the elbow ductingchannels. Based on data from research results, the number of guide vanes and position affects thepressure drop. From the graph shows that the installation of guide vanes to reduce pressure drop whenfluid flows through the elbow. Installation guide vanes with the number five result in the smallest pressuredrop of 9.1%. Efficiency caused by the installation of guide vanes reached 27.6%. Can be concluded thatthe installation of guide vanes on the elbow can be used as a reference in the design of ducting so asreduce the energy consumption.